Reliability of Sino-Nasal Outcome Test in Measuring the Outcome of Septoplasty - Prakash, S; Pradhan, B; Thapa, NM (Nepalese Journal of ENT Head and Neck Surgery, 2012)
Nepalese Journal of ENT Head and Neck Surgery Vol.2 No.1 Issue 1 (Jan-Jun 2011) 8-11 DOI: http://dx.doi.org/10.3126/njenthns.v2i1.6776